Where the past begins : a writer's memoir - Tan, Amy (Ecco, an imprint of HarperCollinsPublishers, 2017)
"From New York Times bestselling author Amy Tan, a memoir on her life as a writer, her childhood, and the symbiotic relationship between fiction and emotional memory"--